SUPERIOR AUTHORITY AND FRAUDULENT IN PROCUREMENT OF GOODS/SERVICES: THE ROLE OF CODE OF ETHICS - Sitanala, Theresia Febiengry (Jurnal Tata Kelola & Akuntabilitas Keuangan Negara, 2019)
An increase in the number of corruption cases in the goods and services procurement at government agencies in Indonesia causes the country to suffer significant losses. This condition proves the noncompliance of the goods and services procurement officials with the code of ethics for the implementation of goods and services procurement. Corruption cases in the goods and services procurement tend to involve goods and services procurement officials, both as Budget User Authorities, Commitment Making Officials, and Technical Implementation Activities Officials. In other words, officials (superiors) use their authority to commit fraud in the goods and services procurement. The purpose of this study is to determine and evaluate the role of the code of ethics on the influence of superior authorities on fraudulent acts in goods and services procurement of government agencies in Indonesia. This study used the laboratory experiments method with the accounting students of Pattimura University, Ambon as the participants and a two-way ANOVA with a 2x3 factorial experimental design as a data analysis technique. The results of this study show that superior authority plays an important role in influencing the occurrence of fraudulent acts in the goods and services procurement, and a code of ethics can reduce it. There is a difference in the tendency to commit fraud in the goods and services procurement when there is a superior authority and no superior authority. The tendency to commit fraud will be smaller for individuals who are asked to read the code of ethics and signatures it compared to only reading the code of ethics and without a code of ethics.